PENGARUH PERENDAMAN KAPUR SIRIH DAN GARAM TERHADAP MUTU TEPUNG BIJI DURIAN (Durio zibethinus Murr) - ', Suparno '; Efendi, Raswen '; ', Rahmayuni ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The aim of this study was to determine the best treatment of the differenceÂ Â solution of slaked lime, salt (NaCl) and soaking time on the quality of flour of durian seed either from the physical, chemical and organic. This study uses a completely randomized design (CRD) with six treatments, with each treatment using 5 grams of slaked lime and 5 grams of salt, 105 grams of durian seeds are used with soaking time of 1, 2, 3 hours in 300 ml of water and three replications. The treatment in this study was PK1 (1 hour long immersion in a solution of slaked lime 5%), PK2 (2 hour long immersion in a solution of slaked lime 5%), PK3 (1 hour long immersion in a solution of slaked lime 5%), PG1 (1 hour long immersion in a solution of salt 5%), PG2 (2 hour long immersion in a solution of salt 5%), PG3 (3 hour long immersion in a solution of salt 5%). The data obtained were analyzed used analysis of variance followed by Duncan's New Multiple Range Test (DNMRT) at 5%. The results showed that the difference in the solution and soaking time is not obvious effect on water content, ash content, starch and fiber content, but has evident influential toward the value of the immersion, pH and sensory assessment. The best treatment in this study was PG3 (3 hour long immersion in a solution of salt 5%) has value of 57.62%, moisture content 8.62%, ash content of 3.72%, starch content 42,35%, fiber content of 4.69%, pH 6.63% and Sensory be accepted by the panelis. Â Keyword : Flour of durian seed, slaked lime and salt.